Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1101/618397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasmodium secretion induces hepatocyte lysosome exocytosis and promotes parasite entry

Abstract: 20The invasion of a suitable host hepatocyte by Plasmodium sporozoites is an essential step in 21 malaria infection. We demonstrate that in infected hepatocytes, lysosomes are redistributed away 22 from the nucleus, and surface exposure of lysosomal-associated membrane protein (LAMP1) is 23 increased. Lysosome exocytosis in infected cells occurs independently of sporozoite traversal. 24Instead, a sporozoite-secreted factor is sufficient for the process. Knockdown of the SNARE 25 proteins involved in lysosome-p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…4 ). This is in agreement with recent findings showing that Plasmodium sporozoites trigger exocytosis of host lysosomes, to facilitate invasion 56 . Notably, other pathogens including another eukaryotic parasite, T. cruzi 48 , but also the bacteria Listeria monocytogenes 57 and Neisseria gonorrhoeae 58 as well as human adenoviruses 59 have also been reported to invade cells by hijacking host cell plasma membrane-repair pathways resulting in ceramide generation.…”
Section: Discussionsupporting
confidence: 94%
“…4 ). This is in agreement with recent findings showing that Plasmodium sporozoites trigger exocytosis of host lysosomes, to facilitate invasion 56 . Notably, other pathogens including another eukaryotic parasite, T. cruzi 48 , but also the bacteria Listeria monocytogenes 57 and Neisseria gonorrhoeae 58 as well as human adenoviruses 59 have also been reported to invade cells by hijacking host cell plasma membrane-repair pathways resulting in ceramide generation.…”
Section: Discussionsupporting
confidence: 94%
“…Multiple screening efforts and other reports (Lopes da Silva et al, 2012;Niklaus et al, 2019;Petersen et al, 2017;Prudencio et al, 2008;Raphemot et al, 2019;Real et al, 2018;Rodrigues et al, 2008;Vijayan et al, 2019) have pointed to the critical role of vesicular transport, including retrograde trafficking (Raphemot et al, 2019), throughout Plasmodium LS infection. Here, we observe an association of Golgi and post-Golgi anterograde vesicles with the parasite, suggesting the parasite sequesters both anterograde and retrograde trafficking of host derived vesicles.…”
Section: Previous Forward-genetic Screens Have Identified Host Factor...mentioning
confidence: 99%
“…The cytoskeleton is a key regulator of deformability, and Plasmodium has been demonstrated to alter host cell actin cytoskeleton during LS development (Gomes-Santos et al, 2012), egress (Burda et al, 2017), and blood stage development (Hale et al, 2017;Warncke and Beck, 2019). We and others previously have demonstrated that the Plasmodium liver stage PV membrane interacts with late endosomes (Petersen et al, 2017), lysosomes (Lopes da Silva et al, 2012;Niklaus et al, 2019;Prado et al, 2015;Risco-Castillo et al, 2015;Vijayan et al, 2019), retrograde vesicles (Raphemot et al, 2019) and autophagic vesicles (Prado et al, 2015;Real et al, 2018;Wacker et al, 2017). As many intracellular pathogens target the host microtubule network to subvert host vesicle trafficking events for their own benefit (Alix et al, 2011;Asrat et al, 2014), we hypothesized that Plasmodium LS parasites actively alters the host cytoskeleton to traffic the host vesicles to PVM.…”
Section: Introductionmentioning
confidence: 99%
“…After hosts are infected with common parasitic protozoans such as Babesia, Plasmodium, and Leishmania, lysosomes in host cells can engulf a large number of parasites [18][19][20]. CTSD belongs to the aspartic protease family.…”
Section: Immune-related Proteinsmentioning
confidence: 99%